Intestinal water absorption varies with expected dietary water load among bats but does not drive paracellular nutrient absorption - Price, Edwin R.; Brun, Antonio; Gontero-Fourcade, Manuel; Fernández-Marinone, Guido; Cruz-Neto, Ariovaldo P. [UNESP]; Karasov, William H.; Caviedes-Vidal, Enrique (My University, 2015)
Rapid absorption and elimination of dietary water should be particularly important to flying species and were predicted to vary with the water content of the natural diet. Additionally, high water absorption capacity was predicted to be associated with high paracellular nutrient absorption due to solvent drag. We compared the water absorption rates of sanguivorous, nectarivorous, frugivorous, and insectivorous bats in intestinal luminal perfusions. High water absorption rates were associated with high expected dietary water load but were not highly correlated with previously measured rates of (paracellular) arabinose clearance. In conjunction with these tests, we measured water absorption and the paracellular absorption of nutrients in the intestine and stomach of vampire bats using luminal perfusions to test the hypothesis that the unique elongated vampire stomach is a critical site of water absorption. Vampire bats’ gastric water absorption was high compared to mice but not compared to their intestines. We therefore conclude that (1) dietary water content has influenced the evolution of intestinal water absorption capacity in bats, (2) solvent drag is not the only driver of paracellular nutrient absorption, and (3) the vampire stomach is a capable but not critical location for water absorption.
Keywords: Desmodus rotundus; Flight; Solvent drag; Stomach; Vampire; Water absorption